An Alternating Skin–Core Structure in Melt Multi-Injection-Molded Polyethylene - Liu, Xianhu; Lian, Meng; Pan, Yamin; Wang, Xin; Zheng, Guoqiang; Liu, Chuntai; Schubert, Dirk W.; Shen, Changyu (Macromolecular Materials and Engineering, 2017)
Shish‐kebab, which is endowed with superior strength and modulus, provides the potential to fabricate self‐reinforced polymer products. However, the injection‐molded product usually exhibits a typical skin–core structure, and the shish‐kebab is only located in an extremely thin shear layer. Therefore, the controlling and tailoring of crystal structures in complex flow field to improve the mechanical properties of the injection‐molded sample are still a great challenge. Herein, for the first time, high‐density polyethylene sample with a novel macroscopic alternating skin–core structure is achieved using a melt multi‐injection molding technique. Results show that, with increasing the amount of melt injection, the layers of skin–core structure increase in the form of arithmetic progression, and therefore the tensile strength of the samples progressively increases due to an increase of shish‐kebab content. This study demonstrates a new approach to achieve multilayer homogeneous materials with excellent tensile strength via macroscopic structural design during the practical molding proces
Keywords: shish-kebab; skin–core structure; injection molding; polyethylene

Annealing Induced Mechanical Reinforcement of Injection Molded iPP Parts. - Pan, Yamin; Liu, Xian Hu; Shi, Suyu; Liu, Chuntai; Dai, Kun; Yin, Rui; Schubert, Dirk W.; Zheng, Guoqiang; Shen, Changyu (Macromolecular Materials and Engineering, 2016)
The mechanical properties and microstructure of injection molded isotactic polypropylene parts with high orientation before and after annealing are analyzed. The mechanical properties of the annealed samples are improved effectively. Through thorough analysis of various structural characterizations, a microstructural model based on the fact that the total length of long period kept constant to analyze the variation of mechanical properties is proposed. It is suggested that the increase of overall crystallinity, the recombination of crystalline phase, and the increase of amorphous phase, respectively, are beneficial for the improvements of the strength, stiffness, and toughness of annealed samples.

Annealing Induced Mechanical Reinforcement of Injection Molded iPP Parts - Pan, Yamin; Liu, Xian Hu; Shi, Suyu; Liu, Chuntai; Dai, Kun; Yin, Rui; Schubert, Dirk W.; Zheng, Guoqiang; Shen, Changyu (Macromolecular Materials and Engineering, 2016)
The mechanical properties and microstructure of injection molded isotactic polypropylene parts with high orientation before and after annealing are analyzed. The mechanical properties of the annealed samples are improved effectively. Through thorough analysis of various structural characterizations, a microstructural model based on the fact that the total length of long period kept constant to analyze the variation of mechanical properties is proposed. It is suggested that the increase of overall crystallinity, the recombination of crystalline phase, and the increase of amorphous phase, respectively, are beneficial for the improvements of the strength, stiffness, and toughness of annealed samples.
Keywords: Injection molding; Mechanical properties; Microstructure; Orientation

Annealing induced rheological and electrical conductivity variations in carbon black filled polymer composites - Liu, Xian Hu; Pan, Yamin; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

Conductivity and phase morphology of carbon black-filled immiscible polymer blends under creep: an experimental and theoretical study. - Pan, Yamin; Liu, Xian Hu; Hao, Xiaoqiong; Schubert, Dirk W. (Physical Chemistry Chemical Physics, 2016)
Blends of carbon black (CB)-filled co-continuous immiscible polystyrene/poly(methyl-methacrylate) (PS/PMMA) with a PS/PMMA ratio of 50/50 and CB selectively located in the PS phase have been prepared by melt blending. The simultaneous evolution of conductivity and phase morphology of blend composites was investigated under shear and in the quiescent state at 200 °C. It was found that shear deformation had a significant influence on the conductivity of the unfilled PS/PMMA blend and its composites, which was attributed to the change of phase morphology during shear. After the shear stress of 10 kPa, the conductivity of PS/PMMA blends filled with 2 vol% of CB decreased by about two orders of magnitude and the phase morphology transformed from a fine co-continuous structure into a highly elongated lamellar structure. The deformation of phase morphology and the decrease of conductivity were weakened upon decreasing the shear stress or increasing the CB concentration. During subsequent recovery, pronounced phase structure coarsening was observed in the mixture and the conductivity increased as well. A simple model describing the behavior of conductivity under shear deformation was derived and utilized for the description of the experimental data. For the first time, the Burgers model was used to describe the conductivity, and the viscoelastic and viscoplastic parameters were deduced by fitting the conductivity under shear. The results obtained in this study provide a deeper insight into the evolution of phase structure in the conductive polymer blend composite induced by shear deformation.

Conductivity and phase morphology of carbon black filled immiscible polymer blends under shear in the molten state - Pan, Yamin; Liu, Xian Hu; Schubert, Dirk W. (Book of Abstracts, 2016)

Conductivity of poly(methyl methacrylate)/polystyrene/carbon black and poly(ethyl methacrylate)/polystyrene/carbon black ternary composite films - Xu, Huagen; Qu, Muchao; Pan, Yamin; Schubert, Dirk W. (Chinese Journal of Polymer Science, 2019)
Both poly(methyl methacrylate) (PMMA)/polystyrene (PS)/carbon black (CB) and poly(ethyl methacrylate) (PEMA)/PS/CB ternary composite films were obtained using solution casting technique to investigate double percolation effect. In both PMMA/PS/CB, PEMA/PS/CB ternary composite films, the CB particles prefer to locate into PS phase based on the results of calculating wetting coefficient, which is also confirmed by SEM images. The conductivity of the films were investigated, the percolation threshold (c) of both ternary composite films with different polymer blend ratio were determined by fitting the McLachlan GEM equation. Conductivity of PMMA/PS/CB ternary composite films shows a typical double percolation effect. However, due to the double emulsion structure of PEMA/PS polymer blends, even the CB only located in PS phase, the PEMA/PS/CB ternary composite films (PEMA/PS = 50/50) shows a higher c, which conflicts with double percolation effect. A schematic diagram combined with SEM images was proposed to explain this phenomeno
Keywords: Double percolation effect; Conductivity; Ternary composite films; Compatibility

Creep and recovery behavior of injection-molded isotactic polypropylene with controllable skin-core structure - Wang, Xin; Pan, Yamin; Qin, Yijing; Voigt, Monika; Liu, Xianhu; Zheng, Guoqiang; Chen, Qiang; Schubert, Dirk W.; Liu, Chuntai; Shen, Changyu (Polymer Testing, 2018)
The creep behavior is one of the most important properties and should be characterized to evaluate long-term durability and reliability of polymeric materials. An alteration of the crystalline structure and morphology in the semicrystalline polymer leads to a change in the creep behavior as well. In this work, in order to understand the creep behavior of different morphologies, a modified injection molding technology with twice melt filling (M2) was used to prepare isotactic polypropylene (iPP) samples with controllable skin-core structure. The different shear layer thicknesses were obtained by adjusting the time intervals of the twice melt filling. Compared with the conventional injection-molded samples (M1), M2 samples present better efficiencies in reducing the creep and recovery response, and the response was strongly influenced by the shear layer thicknesses. For example, the thickness of skin layer of M2 sample with a time interval of 9 s increased approximately 42% and its creep deformation reduced to 52% at 80 °C. It was also found that the creep and recovery strain reduced with decreased temperature or with applied stress. In addition, several theoretical models were used to describe the creep and recovery behavior of M2 samples for a better understanding of the mechanism
Keywords: Creep; Injection molding; PP; Polypropylene; Skin-core structure

Electrical conductivity and mechanical properties of melt-spun ternary composites comprising PMMA, carbon fibers and carbon black - Qu, Muchao; Nilsson, Fritjof; Qin, Yijing; Yang, Guanda; Pan, Yamin; Liu, Xian Hu; Hernández Rodríguez, Gabriel; Chen, Jianfan; Zhang, Chunhua; Schubert, Dirk W. (Composites Science and Technology, 2017)
Keywords: Carbon black; Melt-spinning; Carbon fibers; Electrical properties

Enhancing electrical conductivity of carbon black filled immiscible polymer blends by tuning the morphology - Pan, Yamin; Liu, Xian Hu; Hao, Xiaoqiong; Stary, Zdenek; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

Enhancing the electrical conductivity of carbon black-filled immiscible polymer blends by tuning the morphology - Pan, Yamin; Liu, Xian Hu; Hao, Xiaoqiong; Stary, Zdenek; Schubert, Dirk W. (European Polymer Journal, 2016)
Blends of carbon black (CB)-filled polystyrene (PS) and poly(methyl methacrylate) (PMMA) with different PS/PMMA ratios have been prepared by melt blending in order to obtain conductive polymer composites with a low electrical percolation threshold according to the concept of double percolation. The dependence of the electrical conductivity on the morphology of the composite was examined before and after annealing in the molten state. The electrical conductivity of the composites was highest when the PS and PMMA phases formed a co-continuous structure and CB particles were selectively located and percolated in the PS phase. PS/PMMA (30/70) blends exhibited the lowest electrical percolation threshold of 1.26 vol% CB. A simple model is suggested to explain this effect. After annealing, the CB clearly affected the stabilization of the co-continuous structure. Moreover, the electrical conductivity increased after annealing and the percolation threshold decreased to below 1 vol% CB regardless of PS content. The largest increase in electrical conductivity after annealing was found with PS/PMMA (70/30) blends filled with 1 vol% CB. With increasing PMMA content, this effect became less pronounced. The different behaviors in the composites can be explained by dynamic percolation and decrease in continuity of the CB-filled PS phase induced by structure coarsening.
Keywords: Annealing; Electrical properties; Interface; Phase morphology; Polymer composites

Entanglement network formed in miscible PLA/PMMA blends and its role in rheological and thermo-mechanical properties of the blends - Hao, Xiaoqiong; Kaschta, Joachim; Liu, Xian Hu; Pan, Yamin; Schubert, Dirk W. (Polymer, 2015)
The miscible amorphous/semi-crystalline polymer blends with shape memory potential has received increasing interests in recent years. In this work, the shape memory mechanism of the miscible amorphous PMMA/semi-crystalline PLA blends was investigated using thermo-mechanical and rheological approaches. With the incorporation of PMMA into PLA, a broad glass transition and increased glass transition temperature Tg were observed by differential scanning calorimetry (DSC) measurements. The broadening of glass transition is attributed to the local nanoscale heterogeneities in the miscible blend system which is related to the self-concentration of the components. The degree of molecular entanglement of the blends was derived based on the oscillatory rheological measurements, showing that the dissimilar chains are more likely to entangle with each other than the similar ones, and the entanglement density ve is enhanced with increased PMMA content up to 50% where a 100% recovery of the initial shape is yielded. After that, ve is reduced with the addition of PMMA. The mechanism underlying the shape memory property is further validated by performing the shape memory test on the PLA/PMMA blend films at respective Tg. It is evident that for the semi-crystalline blends (PLA rich), PLA crystallites and molecular entanglement provide physical cross-links for shape recording, while a negative effect of crystallinity on the shape recovery ratio is obtained due to the strain-induced crystallization and chain slippage between the crystalline and amorphous chains. In contrast, for the amorphous blends (PMMA rich), the shape recovery ratio shows a strong positive linear dependence on ve, and the entanglement network is regard as the most important factor in the shape memory performanc
Keywords: Rheological property; Shape memory polymer; Molecular entanglement

Entanglement network formed in miscible PLA/PMMA blends and its role in rheological and thermo-mechanical properties of the blends - Hao, Xiaoqiong; Kaschta, Joachim; Liu, Xian Hu; Pan, Yamin; Schubert, Dirk W. (Polymer, 2015)
The miscible amorphous/semi-crystalline polymer blends with shape memory potential has received increasing interests in recent years. In this work, the shape memory mechanism of the miscible amorphous PMMA/semi-crystalline PLA blends was investigated using thermo-mechanical and rheological approaches. With the incorporation of PMMA into PLA, a broad glass transition and increased glass transition temperature Tg were observed by differential scanning calorimetry (DSC) measurements. The broadening of glass transition is attributed to the local nanoscale heterogeneities in the miscible blend system which is related to the self-concentration of the components. The degree of molecular entanglement of the blends was derived based on the oscillatory rheological measurements, showing that the dissimilar chains are more likely to entangle with each other than the similar ones, and the entanglement density ve is enhanced with increased PMMA content up to 50% where a 100% recovery of the initial shape is yielded. After that, ve is reduced with the addition of PMMA. The mechanism underlying the shape memory property is further validated by performing the shape memory test on the PLA/PMMA blend films at respective Tg. It is evident that for the semi-crystalline blends (PLA rich), PLA crystallites and molecular entanglement provide physical cross-links for shape recording, while a negative effect of crystallinity on the shape recovery ratio is obtained due to the strain-induced crystallization and chain slippage between the crystalline and amorphous chains. In contrast, for the amorphous blends (PMMA rich), the shape recovery ratio shows a strong positive linear dependence on ve, and the entanglement network is regard as the most important factor in the shape memory performanc
Keywords: Rheological property; Shape memory polymer; Molecular entanglement

Intermolecular cooperativity and entanglement network in a miscible PLA/PMMA blend in the presence of nanosilica - Hao, Xiaoqiong; Kaschta, Joachim; Pan, Yamin; Liu, Xian Hu; Schubert, Dirk W. (Polymer, 2016)
Nanosilica filled polylactide (PLA)/Poly(methyl methacrylate) (PMMA) 50/50 blends with varying silica concentrations were prepared by melt mixing. In this work, the effects of silica concentration and the preferential adsorption between silica and the component on the thermo-mechanical and rheological properties of PLA/PMMA blends were systematically investigated. The results of DSC indicate the miscibility of PLA/PMMA/silica nanocomposites in the solid state, and the incorporation of nanosilica does not only increase the glass transition temperature but also extend the broadness of glass transition. Local nanoscale heterogeneities in the miscible blends are proposed due to the self-concentration of the components, and the presence of nanosilica increased the concentration fluctuation and dynamic heterogeneity of the PLA/PMMA blends. A distinct "crater" structure can be observed in the fractured surfaces of the blend nanocomposites. According to the results of SEM and rheological measurements, it was proposed that PLA molecules were selectively adsorbed on the surface of nanosilica, and the preferential adsorption of PLA changed the blend composition in the "crater" structure and the bulk matrix. The phase separation temperature of the filled PLA/PMMA blends was also improved by the incorporation of nanosilica, implying a potential role of nanosilica in improving the phase stability of PLA/PMMA blends. In addition, nanosilica could increase and entanglement density and decrease the entanglement molar mass of the blends in a concentration-dependent manner. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Miscible blend; Nanocomposite; Preferential adsorption

Investigating the electrical conductivity of PMMA/ carbon black and of PS/PMMA/ carbon black blends prior to and after shear - Voigt, Monika; Pan, Yamin; Liu, Xian Hu; Schubert, Dirk W. (Book of Abstracts, 2016)
The electrical conductivity of disk-like poly(methyl methacrylate)/carbon black (PMMA/CB) composite samples with   various CB concentrations as a function of the position was investigated prior to and after a shear process. Novel   electrical conductivity maps of the samples were obtained. It was found that the electrical conductivity from angular   averaging of static samples is independent of the radius regardless of the CB concentrations but strongly   dependent for sheared samples with varied CB concentrations. 1 Additionally, CB filled polystyrene (PS) and PMMA   blends with different PS/PMMA ratio have been fabricated by melt blending to obtain conductive polymer   composites with a low electrical percolation threshold. The electrical conductivity of the composites was highest   when PS and PMMA phases form a co-continuous structure and CB particles were selectively located and   percolated in the PS phase. Moreover, the simultaneous evolution of electrical conductivity and phase morphology   of CB filled co-continuous PS/PMMA (50v/50v) composites was investigated under shear and quiescent melt.   Under shear stress, the conductivity of these blends decreased by about two orders of magnitude and the phase   morphology changed into a strip structure 2 . Impact of shear on the phase morphology become less significant as   CB concentration increased or shear stress decreased. During subsequent recovery, pronounced phase structure   coarsening and conductivity increase were observed in the systems. The results obtained in this study provide a   deeper insight into phase structural and conductivity changes in conductive polymer composite induced by shear   deformation.   1. X. Liu, J. Krückel, G.Q. Zheng, D.W. Schubert, ACS Appl. Mater. Interfaces 2013, 5, 8857   2. Y. Pan, X. Liu, X. Hao, Z. Starý, D.W. Schubert, Europ. Polym. J. 78 (2016) 106–115

Molar mass and temperature dependence of rheological properties of polymethylmethacrylate melt - Lu, Zhili; Pan, Yamin; Liu, Xianhu; Zheng, Guoqiang; Schubert, Dirk W.; Liu, Chuntai (Materials Letters, 2018)
The influence of molar mass and temperature on the rheological properties of polymethylmethacrylate (PMMA) melts was investigated by dynamical mechanical and creep-recovery experiments. The results shown that the steady state viscosities obtained from both experimental modes were in good agreement, and a well linear relationship between the activation energy and molar mass was obtained. The creep compliance of PMMA increased with the molar mass increased or temperature decreased, while the linear steady state recoverable compliance was found to be independent of the molar mass and temperature. Moreover, it was found that the master curves followed the time-temperature superposition principle well in the whole frequency range or time scal
Keywords: Amorphous materials; Creep; Activation energy; Molar mass; Viscosity

Reversal phenomena of molten immiscible polymer blends during creep-recovery in shear - Pan, Yamin; Liu, Xian Hu; Kaschta, Joachim; Liu, Chuntai; Schubert, Dirk W. (Journal of Rheology, 2017)
In this work, the creep- recovery behavior of immiscible poly (styrene)/poly (methyl methacrylate) blends and their pure components in the molten state were systematically investigated. A stationary plateau in the recoverable compliance of pure components is observed. Unexpectedly, for immiscible polymer blends, the recoverable compliances show different phenomena. For blends with a fine co-continuous morphology, the recoverable compliances exhibit a one-reversal phenomenon, whereas a two-reversal phenomenon is found in the blends with a sea-island morphology. Moreover, these reversal behaviors become less pronounced with decreasing temperature, increasing creep stress, increasing annealing time, or incorporation of nanoparticles. Three competitive effects, i.e., the recovery of oriented polymer matrix, the interfacial tension which drives the deformed droplets to their equilibrium shape, and the phase coarsening process, are used here to explain the different behaviors. (C) 2017 The Society of Rheology.

Rheological and electrical behavior of poly(methyl methacrylate)/carbon black composites as investigated by creep recovery in shear - Liu, Xian Hu; Pan, Yamin; Zheng, Guoqiang; Schubert, Dirk W. (Composites Science and Technology, 2016)
The rheological and electrical behavior of poly(methyl methacrylate) (PMMA)/carbon black (CB) composites has been studied as a function of CB concentration by simultaneous electrical and rheological measurements during creep and creep-recovery experiments in the linear and nonlinear regimes. The creep compliance and recoverable compliance were strongly influenced by the CB concentration in the linear regime, especially above the percolation threshold. The creep compliance remained almost unchanged in the linear and nonlinear regimes, but the recoverable compliance was strongly influenced by the creep stress. The electrical conductivity increased under low creep deformation, but under high creep deformation, the electrical conductivity decreased rapidly at the beginning of the creep experiment. After a sufficiently long creep time under shear, the electrical conductivity again increased. The results provide a deeper insight into structural changes in conductive polymer composites induced by shear deformation.
Keywords: Deformation; Electrical properties; Polymer-matrix composites; Rheology

Rheological and Electrical Behavior of Poly(methylmethacrylate)/Carbon Black Composites As Investigated by Creep Recovery in Shear - Liu, Xian Hu; Pan, Yamin; Zheng, Guoqiang; Schubert, Dirk W. (Book of Abstracts, 2016)

The role of conductive pathways in the conductivity and rheological behavior of poly(methyl methacrylate)-graphite composites - Liu, Xian Hu; Pan, Yamin; Hao, Xiaoqiong; Dai, Kun; Schubert, Dirk W. (Journal of Applied Polymer Science: Applied Polymer Symposium, 2016)
Up to now, research on the dynamic process of conductive network formation has tended to focus on composite particles with one‐dimensional geometry, such as carbon black and carbon nanotubes. However, studies on this subject based on fillers with two‐dimensional structure, such as graphite, are rare in the literature. In this work, the dynamic percolation and rheological properties of poly(methyl methacrylate) (PMMA)–graphite composites under an electric field were investigated. The activation energies of conductive network formation and polymer matrix mobility were calculated from the temperature dependence of the percolation time and the zero‐shear viscosity. It was found that the activation energy calculated from the zero‐shear viscosity was not influenced by the electric field in the concentration range investigated, but the electric field had an effect on the activation energy calculated from the percolation time. This finding emphasizes that the electrical and rheological properties have different physical origins
Keywords: self-assembly; conducting polymers; rheology; composites; amorphous

Twisted lamellae in water-assisted injection molded high density polyethylene - Liu, Xian Hu; Pan, Yamin; Peng, Cheng; Hao, Xiaoqiong; Zheng, Guoqiang; Liu, Chuntai; Schubert, Dirk W.; Shen, Changyu (Materials Letters, 2016)
A distinct skin-core-water-channel structure was formed in water-assisted injection molded low molecular weight high density polyethylene. A large number of well-developed banded spherulites were observed in core region. Two types of shish-kebabs, i.e., shish-kebabs without and with twisted lamellae, were appeared in both skin and water-channel region. The results imply that the formation mechanisms of twisted lamellae in banded spherulites and shish-kebabs are different, but both depend on the level of applied shear stress. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Banded spherulites; Microstructure; Twisted lamellae; X-ray techniques

Viscoelastic and electrical behavior of poly(methyl methacrylate)/carbon black composites prior to and after annealing - Pan, Yamin; Liu, Xian Hu; Kaschta, Joachim; Hao, Xiaoqiong; Liu, Chuntai; Schubert, Dirk W. (Polymer, 2017)
Keywords: Carbon black; Creep-recovery; Polymer nanocomposites; Viscoelastic properties